RELAÇÃO PROFESSOR-ALUNO NA FORMAÇÃO INICIAL DOCENTE: REPRESENTAÇÕES SOCIAIS CONSTRUÍDAS - Almeida, Edilene Freitas Silva de (2015)
This study analyzes the influence of the relationship professor-student in the initial teaching preparation and in his professional practice, based on the constituent elements of the Language Arts graduated students social representations, from the Basic Teachers Education Special Program (PROEB/UFMA). During the development of the investigation, bibliographic and field researches were applied. For the bibliographic study of the social representations, some authors established the direction of the analysis: Moscovici (2012); Jodelet (1993; 2009); Guareschi (2008; 2012); Bonfim (2007); Alves-Mazotti (2008); Farr (2012); Menin, Shimizu and Lima (2009); Spink (1993, 2012); Villas Bôas and Sousa (2011) among others. In order to understand how the relationship professor-student was established in the initial preparation, a history retrieval of the University in Brazil constitution was done, because it is understood that this relationship is affected by the conditioning of adopted conceptions by the universitary educational program. Thus, authors like Freire (1996, 2005), Anísio Teixeira (1989), Pimenta and Anastasiou (2002), Shigunov Neto and Maciel (2008), Coelho and Vasconcelos (2009), Soares et al (2002), Fávero (2006), Passos (2004), Cunha (2010), were studied among others. As data collection instruments, the semistructured interview and the profile questionnaire were used. The interview, which is a capable instrument to attach the experience of the other person and permits the elucidation of his behavior, takes into consideration the self perspective of the involved subjects. The profile questionnaire to know aspects related to the context of the subjects life, indispensable element in the researches of social representations. The data treatment was elaborated through the content analysis technique that allows the description, systematization, inference and interpretation of qualitative and quantitative studies (BARDIN, 1977). The content analysis procedure of the interviews was done according to the following operational steps: the corpus constitution, composed of twenty interviews; a floating reading which allowed the subcategories codification of similar themes; the subcategories composition, inffered by the group of thematic units; the definition of the categories, that consists of a wider concept that synthesizes the knowledge, and, at last the categories description, that are the detailed discussion and analysis of the categorization in the light of the theory and the studied object (COUTINHO, 2011; SARAIVA, 2007). From the analysis, it was possible to infer the social representations of the graduated students about the relationship professor-student lived in the graduation period. The results portray that the social representations lived and/ or constructed in the everyday classroom situations or in the previous phase influence the students learning, as well as affect in the professional practice. Therefore, as this relationship is, essencially, interactive, requires a dialogical space in which formed representations or the ones which are in formation are endorsed in respect and confidence, creating a favorable climate to the development of teaching-learning process.